The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/1759-7714.14393
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral genetic and immune microenvironmental heterogeneity in T4N0M0 (diameter ≥ 7 cm) non‐small cell lung cancers

Abstract: Background Starting with low metastatic capability, T4N0M0 (diameter ≥ 7 cm) non‐small cell lung cancers (NSCLCs) constitute a unique tumor subset, as with a large tumor size but no regional or distant metastases. We systematically investigated intratumoral heterogeneity, clonal structure, chromosomal instability (CIN), and immune microenvironment in T4N0M0 (≥7 cm) NSCLCs. Methods Whole‐exome sequencing, RNA sequencing, and multiplex immunohistochemistry (mIHC) staining were conducted to analyze 24 spatially s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Collectively, these observations indicate that the degree of CIN significantly impacts the composition of immune cell populations within the TME, thereby establishing a nexus between CIN, immune cell infiltration, and their collective impact on the complex landscape of tumourigenesis [89,90]. As such, the cellular composition of the TME has important implications for the immune response to cancer cells, for tumour growth, and for therapeutic strategies.…”
Section: Cellular Components In the Tmementioning
confidence: 93%
See 2 more Smart Citations
“…Collectively, these observations indicate that the degree of CIN significantly impacts the composition of immune cell populations within the TME, thereby establishing a nexus between CIN, immune cell infiltration, and their collective impact on the complex landscape of tumourigenesis [89,90]. As such, the cellular composition of the TME has important implications for the immune response to cancer cells, for tumour growth, and for therapeutic strategies.…”
Section: Cellular Components In the Tmementioning
confidence: 93%
“…The cellular composition of the TME is heavily influenced by a CIN phenotype and resulting aneuploidy in cancer cells as a result of the interaction of cells with CIN and the immune system [84][85][86][87]. However, various contrasting effects of more complex aneuploidy landscapes were reported: some studies have observed increased T cell and macrophage infiltration due to increased immunogenicity from tumour cell genetic diversity, while other studies have shown that tumours with CIN foster an immune-suppressive milieu, preventing the primary CIN-induced immune responses [87][88][89][90]. Likely, these contrasting findings relate to the stage of the tumour, with early CIN + tumours recruiting a tumour-suppressive immune landscape and late tumours circumventing this [91,92].…”
Section: Cellular Components In the Tmementioning
confidence: 99%
See 1 more Smart Citation